Genetic diversity in a population of rhinoclemmys nasuta (testu-dines:geoemydidae) associatted with an insular locality in the chocó biogeographic region (2014)
Characterization of the genetic diversity of Rhinoclemmys nasuta population inhabits Isla Palma (Malaga Bay, Valle del Cauca)was carried out using three microsatellite systems (Cm72, Cm58 and Cm3). In this locality, individuals of  R. nasutaare widely distributed in the inland streams and creeks system. 100 to 200 ìL of peripheral blood was taken off from 10 turtles in five streams of theisland, preserving samples in in a 0.5 M EDTA. DNA was extracted using Salting-out and Chelex 100 solutiontechniques. PCR amplified products were visualized and measured in polyacrylamide gels (19:1) to 8 % silver nitrate. Successful amplification products were obtained for all systems analyzed, two of which (Cm72 and Cm3) were found to be monomorphic, while the system Cm58had a high PIC (0.698) allowing to estimate the genetic diversity of this population. The observed heterozygosity was low (Ho = 0.26 ) and inbreeding indices FIS and FIT were high (0.67857 and 0.67881 ), indicating an excess of homozygotes in each of the rivers and for the all population. The molecular analysis of variance suggested that there is no difference in genetic structure of the population (FST= 0.00075,p= 0.95112 ). Therefore, the results suggest that the genetic diversity of R. nasutapopulation in Isla Palma was low and exhibited a highly inbred index.DIVERSIDAD GENÉTICA EN UNA POBLACION DE Rhinoclemmys nasuta (TESTUDINES:GEOEMYDIDAE) ASOCIADA A UN AMBIENTE INSULAR DEL CHOCÓ BIOGEOGRÁFICOSe realizó la caracterización de la diversidad genética de la población de Rhinoclemmys nasuta, que habita en la localidad insular de Isla Palma, Bahía Málaga (Valle del Cauca, Colombia), utilizando tres sistemas de microsatélites (Cm72, Cm58 y Cm3). En esta localidad, R. nasuta se encuentra ampliamente distribuida en los sistemas de riachuelos y quebradas presentes. Se tomaron entre 100 a 200 µL de sangre periférica de 10 tortugas en cinco riachuelos, preservando las muestras en una solución 0,5 M de EDTA y el ADN fue extraído mediante las técnicas de Salting-out y Chelex 100. Los productos amplificados por PCR fueron visualizados y medidos en geles de poliacrilamida (19:1) al 8% con nitrato de plata. Se obtuvieron productos amplificados exitosos para todos los sistemas analizados, dos de los cuales (Cm72 y Cm3) resultaron ser monomórficos, mientras que el sistema Cm58 presentó un PIC alto (0,698) permitiendo estimar la diversidad genética de esta población. La heterocigosidad observada fue baja (Ho = 0,26) y los índices de endogamia FIS y FITfueron altos (0,67857 y 0,67881), indicando un exceso de homocigotos en cada uno de los ríos y para la población total. El Análisis Molecular de Varianza sugirió que no existe estructura genética diferencialen esta población (FST = 0.00075; p = 0.95112). En conclusión los resultados sugieren que la diversidad genética de la población de R. nasuta en Isla Palma es baja, siendo una población altamente endogámica.